Aliens in medieval law : the origins of modern citizenship - Kim, Ki-ch'ang (Cambridge studies in English legal history., 2000)
Keechang Kim makes full use of medieval and early modern sources in this original reinterpretation of the legal aspects of feudalism, proposing a radical new understanding of the genesis of the modern legal regime. This innovative study will interest academics, lawyers, and students of legal history, immigration and minority issues.